2017
DOI: 10.1177/0093854816686631
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury and Recidivism Among Returning Inmates

Abstract: In recent years, there has been a surge in research that examines the relationship between traumatic brain injury (TBI) and involvement in the criminal justice system. However, the bulk of this research has been largely retrospective and descriptive, comparing rates of TBI in the offending population with the rates of TBI in the general population. Although findings from these studies indicate a higher prevalence of TBI in the offending population, virtually no studies have examined whether those with TBI are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 79 publications
1
39
0
Order By: Relevance
“…Shiroma and colleagues,74 in a US state-wide study over 11 years using linked hospital and justice datasets of 17 569 inmates, found that males and females with TBI had significantly higher rates of violent infractions. Ray and Richardson75 did a longitudinal, prospective, follow-up study of 151 inmates released from incarceration during a period of 12–30 months. At 12 months postrelease, 63% of those without TBI had not recidivated, whereas 48% of TBI had not.…”
Section: Tbi Prevalence Studies In Offender Populationsmentioning
confidence: 99%
“…Shiroma and colleagues,74 in a US state-wide study over 11 years using linked hospital and justice datasets of 17 569 inmates, found that males and females with TBI had significantly higher rates of violent infractions. Ray and Richardson75 did a longitudinal, prospective, follow-up study of 151 inmates released from incarceration during a period of 12–30 months. At 12 months postrelease, 63% of those without TBI had not recidivated, whereas 48% of TBI had not.…”
Section: Tbi Prevalence Studies In Offender Populationsmentioning
confidence: 99%
“…While a limited number of previous studies have reported findings in line with this alternative, spurious hypothesis (Guberman et al 2018), a significant number of additional studies have reported findings that fall more directly in line with a causal hypothesis. For example, studies have examined behavioral trends after sustaining a brain injury in an effort to prevent reverse causation (Connolly and McCormick 2019;Fazel et al 2011;Jackson et al 2017;Ray and Richardson 2017;Sariaslan et al 2016aSariaslan et al , 2016bSchwartz et al 2017). For example, Fazel et al (2011) examined Swedish population registers and found that those who sustained a brain injury were more than three times more likely to commit a violent crime post injury relative to their uninjured counterparts (aOR = 3.3, 95% CI = 3.1-3.5).…”
Section: Brain Injury Neurological Deficits and Antisocial Behaviormentioning
confidence: 99%
“…First, morality and moral decision-making have a deep-rooted neurological basis with multiple brain structures and systems implicated in the development of morality and, in turn, moral disengagement (Moll et al 2005;Pascual et al 2013). Second, previous research has provided substantial evidence linking both moral disengagement (Gil-Fenoy et al 2018;Morgan and Lilienfeld 2000;Raine 1997) and brain injury (Connolly and McCormick 2019;Fazel et al 2011;Jackson et al 2017;Ray and Richardson 2017;Sariaslan et al 2016aSariaslan et al , 2016bSchwartz 2019;Schwartz et al 2017Schwartz et al , 2018 to behavior problems. Third, studies have identified neurological dysfunction within those that have sustained previous brain injuries as falling directly in line with moral disengagement (Beauchamp et al 2013(Beauchamp et al , 2019 or similar to the symptomology, with executive dysfunction playing an especially important role (Bechara et al 2000;Friedman et al 2008).…”
Section: The Current Studymentioning
confidence: 99%
“…Within the custodial estate, offenders with TBI have been shown to have higher rates of infractions than offenders without TBI which have been attributed to higher levels of aggression (22). Prisoners with TBI are at a significantly heightened risk of mental illness (23)(24)(25) with increased aggression and behavioural problems serving to increase their isolation and vulnerability. The removal of liberty and contact with loved ones leads to reduced social support and increased isolation, which is a contributory factor towards poor mental health (26).…”
Section: Introductionmentioning
confidence: 99%